ПРАВОВЫЕ ПРОБЛЕМЫ ЮРИДИЧЕСКИХ ФОРМ РЕАЛИЗАЦИИ ОСУЩЕСТВЛЕНИЯ АДМИНИСТРАТИВНЫХ ПРОЦЕДУР (Journal of actual problems of jurisprudence, 2019)
The scientific article is devoted to the reseach of the theoretical and practical problems of the introduction and effective use of the social-legalcontrol for securing of the defence of the citizens`s rights on the executive power organs`s activity of the Republic of Kazakhstan.